2014
DOI: 10.1186/1471-2482-14-29
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up and retrospective study on 533 gastric cancer cases

Abstract: BackgroundGastric cancer (GC) is the third leading cause of cancer death in China and the outcome of GC patients is poor. The aim of the research is to study the prognostic factors of gastric cancer patients who had curative intent or palliative resection, completed clinical database and follow-up.MethodsThis retrospective study analyzed 533 GC patients from three tertiary referral teaching hospitals from January 2004 to December 2010 who had curative intent or palliative resection, complete clinical database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…In addition, post-hoc analysis of randomized trials in a recent meta-analysis of extended lymphadenectomy for gastric cancer suggested a possible survival benefit in Stage T3+ tumors, non-randomized comparisons revealed the benefit in Stage II and IIIA, and observational studies reported better survival outcomes of D2 surgery (14). In a recent retrospective study conducted on 533 gastric cancer patients, the median survival by Stages IIIB and IIIC were 28.0 and 14.8 mo., and D2-LND appeared as the major prognosticator of survival (15). These findings are consistent with our results in which patients with gastric cancer and the pathological Stage III and beyond, that had at least a loco-regional or a distant metastases, had benefited much from D2-LND with regard to OS, with a median OS of 20.0±5.0 months.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, post-hoc analysis of randomized trials in a recent meta-analysis of extended lymphadenectomy for gastric cancer suggested a possible survival benefit in Stage T3+ tumors, non-randomized comparisons revealed the benefit in Stage II and IIIA, and observational studies reported better survival outcomes of D2 surgery (14). In a recent retrospective study conducted on 533 gastric cancer patients, the median survival by Stages IIIB and IIIC were 28.0 and 14.8 mo., and D2-LND appeared as the major prognosticator of survival (15). These findings are consistent with our results in which patients with gastric cancer and the pathological Stage III and beyond, that had at least a loco-regional or a distant metastases, had benefited much from D2-LND with regard to OS, with a median OS of 20.0±5.0 months.…”
Section: Discussionsupporting
confidence: 91%
“…Univariate analysis showed that sex was not an independent prognostic factor of GC, which was keeping with previous studies [20][21]. We indicated that prognosis was associated with tumor size, location, type of gastrectomy and BMI.…”
Section: Discussionsupporting
confidence: 90%
“…There was no statistical difference between them [18]. Otherwise, univariate and multivariate analysis both indicated that the degree of differentiation and radical treatment were two independent prognostic factors of GC, consistent with previous studies [19][20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In patients with both HIPEC and surgery, the rate of liver, lung, and bone metastases, as well as peritoneal metastases recurrence, was also lower. 9 A large meta-analysis by Zeng et al, 10 also showed that treatment with HIPEC was an independent prognostic factor that increased survival times in patients with gastric cancers. A study by Ji et al combined the published clinical trials on CRS-HIPEC.…”
Section: The Effect Of Hipec On Gastric Cancer Mortalitymentioning
confidence: 99%